Ethnography and user-centered design to inform context-driven implementation. Issue 1 (5th July 2021) - Haines, Emily R; Kirk, M Alexis; Lux, Lauren; Smitherman, Andrew B; Powell, Byron J; Dopp, Alex; Stover, Angela M; Birken, Sarah A
Abstract: Despite pervasive findings pointing to its inextricable role in intervention implementation, context remains poorly understood in implementation science. Existing approaches for describing context (e.g., surveys, interviews) may be narrow in scope or superficial in their elicitation of contextual data. Thus, in-depth and multilevel approaches are needed to meaningfully describe the contexts into which interventions will be implemented. Moreover, many studies assess context without subsequently using contextual information to enhance implementation. To be useful for improving implementation, though, methods are needed to apply contextual information during implementation. In the case example presented in this paper, we embedded an ethnographic assessment of context within a user-centered design approach to describe implementation context and apply that information to promote implementation. We developed a patient-reported outcome measure-based clinical intervention to assess and address the pervasive unmet needs of young adults with cancer: the Needs Assessment & Service Bridge (NA-SB). In this paper, we describe the user-centered design process that we used to anticipate context modifications needed to deliver NA-SB and implementation strategies needed to facilitate its implementation. Our ethnographic contextual inquiry yielded a rich understanding of local implementation context and contextual variation across potential scale-up contexts. Other methods from user-centered design (i.e., translation tables and a design team prototyping workshop ) allowed us to translate that information into specifications for NA-SB delivery and a plan for implementation. Embedding ethnographic methods within a user-centered design approach can help us to tailor interventions and implementation strategies to their contexts of use to promote implementation. Lay Summary: The field of implementation science studies how to better integrate research evidence into practice. To accomplish this integration, it is important to understand the contexts into which interventions are being implemented. For example, implementation may be influenced by contextual factors such as patient/provider beliefs about an intervention, budget constraints, leadership buy-in, an organization's readiness to change, and many others. Understanding these factors upfront can allow us to adapt interventions to better suit context (e.g., tailoring intervention content to patients' needs), change context to make it more ready for implementation (e.g., changing provider workflow to accommodate an intervention), and anticipate strategies that may be needed to implement an intervention (e.g., delivering training on the intervention to providers). To do this, the field of implementation science is in need of methods for assessing context and using that information to improve implementation. In this paper, we present several methods, including ethnography and methods from user-centered design, for using context to inform implementation efforts. Abstract : Using a case example in young adult cancer care, we describe novel methods for assessing the context in which an intervention will be used and leveraging that information to improve implementation of the intervention.